Alkaline Phosphatase, an Unconventional Immune Protein - Rader, Bethany A. (Frontiers in Immunology, 2017)
Recent years have seen an increase in the number of studies focusing on alkaline phosphatases (AP), revealing an expanding complexity of function of these enzymes. Of the four human AP proteins, most is known about tissue non-specific AP (TNAP) and intestinal AP (IAP). This review highlights current understanding of TNAP and IAP in relation to human health and disease. TNAP plays a role in multiple processes including bone mineralization, vitamin B6 metabolism and neurogenesis, is the genetic cause of hypophosphatasia, influences inflammation through regulation of purinergic signaling, and has been implicated in Alzheimer’s disease. IAP regulates fatty acid absorption and has been implicated in the regulation of diet induced obesity and metabolic syndrome. IAP and TNAP can dephosphorylate bacterial derived lipopolysaccharide (LPS), and IAP has been identified as a potential regulator of the composition of the intestinal microbiome, an evolutionarily conserved function. Endogenous and recombinant bovine APs and recombinant human APs are currently being explored for their potential as a pharmacological agents to treat AP associated diseases and mitigate multiple sources of inflammation. Continued research on these versatile proteins will undoubtedly provide insight into human pathophysiology, biochemistry, and the human holobiont.